"Very sad, but it works": One pupil's assessment career in religious education - Fancourt, N (2013)
This article combines two under-researched issues: the role and effect of assessment in religious education and the effect of assessment regimes on the construction of learner identities. It describes the context to assessment in English religious education. Then generic arguments about summative and formative assessment are reviewed, and the notion of assessment careers is introduced. The practitioner research methodology is described, before analyzing the data from one pupil, which shows how he combined elements of two types of learner identity, including the ability to reflect on wide aspects of his learning in religious education. The implications for conceptualizing learner identities and for assessment in religious education are considered. © Taylor and Francis Group, LLC.